Measurement of powder bed density in powder bed fusion additive manufacturing processes. (5th October 2016) - Jacob, G; Donmez, A; Slotwinski, J; Moylan, S
Abstract: Many factors influence the performance of additive manufacturing (AM) processes, resulting in a high degree of variation in process outcomes. Therefore, quantifying these factors and their correlations to process outcomes are important challenges to overcome to enable widespread adoption of emerging AM technologies. In the powder bed fusion AM process, the density of the powder layers in the powder bed is a key influencing factor. This paper introduces a method to determine the powder bed density (PBD) during the powder bed fusion (PBF) process. A complete uncertainty analysis associated with the measurement method was also described. The resulting expanded measurement uncertainty, U PBD ( k   =  2), was determined as 0.004 g · cm −3 . It was shown that this expanded measurement uncertainty is about three orders of magnitude smaller than the typical powder bed density. This method enables establishing correlations between the changes in PBD and the direction of motion of the powder recoating arm.